Hidden [large type] - Michaels, Fern (Michaels, Fern. Lost and found novel, 2021)
"At first glance, few would guess that Luna and Cullan Bodman are siblings. When the two launch their furniture restoration shop, little do they know their talents may be their only defense in a matter of life and death. When Luna gets a strange sense about a piece Cullan just acquired, the two find themselves uniting to solve a mystery that has far-reaching consequences. Soon, they're on the hunt for a woman in danger--never knowing there are some who'll stop at nothing to claim what they believe is theirs. Luna and Cullan know they can rely on each other--and this time, their lives may depend on it"--Page 4 of cover.